Pengaruh Kualitas Pelayanan, Physical Evidence, dan Kepercayaan Terhadap Kepuasan Pelanggan - Septiani, Metia; Alim, Syahrul (MBIA, 2024)
The development of tourist attractions is strongly supported by the availability of infrastructure and complementary amenities, particularly hotels. As a crucial service industry component, the hotel sector plays a vital role in fostering economic growth. A hotel is defined as a commercial establishment offering lodging, food, beverages, and other services to the public, either in whole or part of its premises. This study investigates the influence of service quality, physical evidence, and trust on customer satisfaction, specifically focusing on the Java Palace Hotel in Cikarang. A total of 259 hotel customers participated as respondents. Data were analyzed using SmartPLS 4.0 with the Structural Equation Modeling (SEM) approach via Partial Least Squares. The results reveal that service quality exerts a positive and significant effect on customer satisfaction, as indicated by a t-statistic of 2.361 (> 1.96) and a p-value of 0.008 (< 0.05). Similarly, physical evidence significantly and positively influences customer satisfaction, supported by a t-statistic of 3.305 (> 1.96) and a p-value of 0.001 (< 0.05). Trust also demonstrates a positive and significant impact on customer satisfaction, with a t-statistic of 2.604 (> 1.96) and a p-value of 0.009 (< 0.05). These findings highlight the critical role of maintaining superior service quality, tangible service environments, and customer trust in enhancing customer satisfaction within the hospitality industry. Keywords: service quality, physical evidence, trust, customer satisfaction.   Abstrak   Keberadaan fasilitas dan infrastruktur pendukung seperti hotel, merupakan salah satu aspek penting yang mendukung perkembangan objek pariwisata. Usaha akomodasi jasa atau hotel ini menjadi salah satu penyumbang tertinggi bagi pertumbuhan ekonomi pada sektor perekonomian. Hotel secara khusus didefinisikan sebagai jenis akomodasi yang memanfaatkan sebagian atau seluruh bangunannya untuk menyediakan jasa penginapan, makanan, minuman, serta layanan lain secara komersial kepada masyarakat umum. Penelitian ini memiliki tujuan untuk mengetahui seberapa besar kualitas pelayanan, physical evidence, dan kepercayaan terhadap kepuasan pelanggan Java Palace Hotel Cikarang. Responden penelitian ini adalah pelanggan Java Palace Hotel Cikarang berjumlah 259 orang. Teknik pengolahan data dalam penelitian ini menggunakan SmartPLS 4.0 SEM (Partical Least Square-Structural Equation Modeling). Hasil dari penelitian ini menunjukkan bahwa terdapat pengaruh positif dan signifikan antara kualitas pelayanan terhadap kepuasan pelanggan Java Palace Hotel Cikarang. Hal ini dibuktikan dengan nilai p-value sebesar 0,018 < 0,05 serta nilai t-statistic 2,361 > 1,96. Selain itu, physical evidence juga terbukti berpengaruh positif dan signifikan terhadap kepuasan pelanggan Java Palace Hotel Cikarang, dengan nilai p-value 0,001 < 0,05 dan nilai t-statistic 3,305 > 1,96. Serta kepercayaan juga berpengaruh secara positif dan signifikan terhadap kepuasan pelanggan Java Palace Hotel Cikarang sebesar p-value 0,009 < 0,05 dan nilai t-statistic 2,604 > 1,96. Kata kunci: kualitas pelayanan, bukti fisik, kepercayaan, kepuasan pelanggan.